Understanding the pathways to improved diets from the production of nutritious and marketable commodities - Aberman, Noora-Lisa; Roopnaraine, Terry (International Food Policy Research Institute, 2015)
Value chains and agricultural commercialization are increasingly being promoted as mechanisms for agricultural transformation, inclusive growth, and, more recently, improving food security and diets. Views of commercialization in agricultural development discourse have fluctuated over the years. Initially framed in terms of moving subsistence farmers into cash cropping and specialization, and subsequently criticized for exposing the poor to the high risk of engaging in commodity markets, the discourse shifted over a decade ago to include commercialization in terms of its effects on nutrition (Alderman 1987; Kennedy and Cogill 1987; Dewalt 1993; Peters and Herrera 1994; von Braun 1995). Theoretically, market-oriented production should allow farmers to increase their incomes and purchase more nutritious foods. However, there is very little empirical understanding of the pathways through which such production impacts diets and under what circumstances. What is clear is that there are a variety of constraints posed by commercial farming that can impede positive dietary changes. These include the tendency of men to control income from cash crops, the inherent price instability of cash crops, and the tendency to spend lumpy income (income based on few irregular payments in the year) on non-food items (DeWalt 1993).